Building Capacity in Post-Conflict Countries - McKechnie, Alastair J. (World Bank, Washington, DC, 2012)
This note looks at the challenge of capacity building in post conflict countries, including at options for creating capacity, and the trade-offs between speed, and longer-term impact, the need to ensure that aid management agencies include sunset provisions, and six proposed general lessons for more sustainable capacity building. Rebuilding institutions is much more difficult than rebuilding damaged infrastructure. Capacity building is an enormous challenge, a challenge that requires imagination, cooperation, and hard work among those who seek to improve the conditions of conflict-affected countries.